2019
DOI: 10.1177/0743915619864543
|View full text |Cite
|
Sign up to set email alerts
|

Credible Effects: The Impact of Disclosure of Material Connections Within Online Product Reviews

Abstract: Online product reviews are an influential source of information for consumers. With pressures to have readily available reviews, businesses must determine the best strategy for obtaining them. In 2009, for the first time in 29 years, the Federal Trade Commission (FTC) updated endorsement guidelines to address concerns over possible deception within online reviews. Since that time, the FTC has issued four additional statements underlining its concerns and providing additional examples of how to comply. In 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A study analyzing online consumer reviews using a sentiment mining approach found that their length and longevity positively influenced their readership and helpfulness (Salehan and Kim, 2016). Some reviewers have never purchased or tried the product and are providing fake reviews for self-gain, whereas others are incentivized to submit online posts (Steward et al , 2020). In the case of incentivized WOM, the incentivization process can induce biased self-interest on the side of the recommender (Pongjit and Beise-Zee, 2015).…”
Section: Conceptual Framework: Deception In Consumer Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study analyzing online consumer reviews using a sentiment mining approach found that their length and longevity positively influenced their readership and helpfulness (Salehan and Kim, 2016). Some reviewers have never purchased or tried the product and are providing fake reviews for self-gain, whereas others are incentivized to submit online posts (Steward et al , 2020). In the case of incentivized WOM, the incentivization process can induce biased self-interest on the side of the recommender (Pongjit and Beise-Zee, 2015).…”
Section: Conceptual Framework: Deception In Consumer Reviewsmentioning
confidence: 99%
“…This situation is even more problematic, considering that the influence of consumer review volume and valence is still debated in the literature (Kordrostami et al , 2021). Even the Federal Trade Commission (FTC) updated its guidelines for endorsements in 2009, in response to pressures from consumer groups, requiring the identification of any material connection between the seller and the reviewer, and took legal measures in multiple fake review cases (FTC, 2009; Plotkina et al , 2020; Steward et al , 2020). Studies have also discussed regulatory intervention to prohibit the use of deceptive consumer communications (Malbon, 2013; Mayzlin et al , 2014; Plotkina et al , 2020; Steward et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressured to provide more product reviews, some companies incentivize reviews or have their own employees write them. The FTC guidelines require that any material connection between reviewer and seller should be stated "clearly and conspicuously" (in Steward et al 2020). Consumers are not as skeptical as sometimes thought-they assume a review does not have a material connection unless otherwise stated (Steward et al 2020).…”
Section: Online Reviews and Marketing System Effectivenessmentioning
confidence: 99%
“…The FTC guidelines require that any material connection between reviewer and seller should be stated "clearly and conspicuously" (in Steward et al 2020). Consumers are not as skeptical as sometimes thought-they assume a review does not have a material connection unless otherwise stated (Steward et al 2020). Mayzlin (2006) shows that firms sometimes pretend their promotion is a consumer recommendation and manipulate online consumer conversations.…”
Section: Online Reviews and Marketing System Effectivenessmentioning
confidence: 99%